Study of the effects of adapted Tango and multidimensional intervention in pREvention of dementia in agiNG: developing healTHy lifestyle programs (STRENGTH Project)—the experimental protocol of a prospective randomised controlled trial - Giuli, Cinzia (Aging Clin Exp Res, 2020)
BACKGROUND: Dementia represents a key health issue for older adults, with negative consequences on psycho-social and functional status. Treatments that counteract cognitive deficits in mild cognitive impairment (MCI) are needed to prevent or delay it. AIM: To describe the experimental protocol of the STRENGTH Project. This study investigates a multimodal intervention in older adults with MCI to improve cognitive, functional, biochemical and psycho-social aspects. METHODS: The prospective randomised controlled trial will enrol 300 subjects with MCI (age ≥ 60 years). Participants will be randomly assigned to: (a) the experimental group, which will undergo sessions of adapted tango, music therapy, engagement in social activities, cognitive intervention and psycho-education for 6 months or (b) the control group, which will receive psycho-education and advice on healthy lifestyle for 6 months. All outcomes will be analysed before intervention (baseline), immediately after termination (follow-up 1), after 6 months (follow-up 2) and after 2 years (follow-up 3). DISCUSSION: We expect that the findings of this multidisciplinary study will be useful to optimize clinical and psycho-social interventions for improving cognitive and functional status of subjects with MCI. CONCLUSIONS: This project could have a meaningful impact on National Health Systems by providing clues on multidisciplinary management of older adults affected by cognitive decline to prevent dementia.